2006
DOI: 10.1016/j.yfrne.2006.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal neuroplasticity induced by early-life stress: Functional and molecular aspects

Abstract: Whereas genetic factors contribute crucially to brain function, early-life events, including stress, exert long-lasting influence on neuronal function. Here, we focus on the hippocampus as the target of these early-life events because of its crucial role in learning and memory. Using a novel immaturerodent model, we describe the deleterious consequences of chronic early-life 'psychological' stress on hippocampus-dependent cognitive tasks. We review the cellular mechanisms involved and discuss the roles of stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
138
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(146 citation statements)
references
References 153 publications
5
138
0
Order By: Relevance
“…While we find no changes in Crhr2 expression in our study, data from previous maternal stress studies in rodents yielded mixed results regarding changes in the central expression of this gene (Vazquez et al, 2003;Plotsky et al, 2005;Bravo et al, 2011). In line with our findings, increased Crhr1 mRNA expression in the amygdala (Bravo et al, 2011) and hippocampus (Fenoglio et al, 2006;Ivy et al, 2010;O'Malley et al, 2011) was also found in adult rodents subjected to maternal stress during the early postnatal period. In addition, previous evidence focused in the dorsal raphe nucleus identified juvenility and adolescence as periods of vulnerability for the modulation of the CRH system by stress (Lukkes et al, 2009).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…While we find no changes in Crhr2 expression in our study, data from previous maternal stress studies in rodents yielded mixed results regarding changes in the central expression of this gene (Vazquez et al, 2003;Plotsky et al, 2005;Bravo et al, 2011). In line with our findings, increased Crhr1 mRNA expression in the amygdala (Bravo et al, 2011) and hippocampus (Fenoglio et al, 2006;Ivy et al, 2010;O'Malley et al, 2011) was also found in adult rodents subjected to maternal stress during the early postnatal period. In addition, previous evidence focused in the dorsal raphe nucleus identified juvenility and adolescence as periods of vulnerability for the modulation of the CRH system by stress (Lukkes et al, 2009).…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, increasing CRH drive occurring specifically in the central amygdala through lentiviral-induced neuropeptide overexpression was also found to enhance anxiety-like (Flandreau et al, 2012) and depression-like (Keen-Rhinehart et al, 2009) behaviors in rats. Enhanced CRHR1 expression in the hippocampus has been linked with impaired cognitive function induced by early life stress (Fenoglio et al, 2006;Ivy et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that the effects of stress on the central nervous system vary as a function of the age at which stress is imposed (reviewed in McEwen, 1 Sanchez et al, 2 Welberg and Seckl, 3 Avishai-Eilner et al, 4 Levine, 5 Miller and O'Callaghan 6 and Fenoglio et al 7 ). For example, prenatal stress has been shown to 're-program' or 'imprint' both neuroendocrine and behavioral responses to subsequent stress throughout the lifetime (see Avishai-Eilner et al, 4 Fenoglio et al, 7 Wadhwa et al, 8 Welberg et al 9 and Weinstock 10 for recent reviews).…”
Section: Introductionmentioning
confidence: 99%
“…For example, prenatal stress has been shown to 're-program' or 'imprint' both neuroendocrine and behavioral responses to subsequent stress throughout the lifetime (see Avishai-Eilner et al, 4 Fenoglio et al, 7 Wadhwa et al, 8 Welberg et al 9 and Weinstock 10 for recent reviews). Neuroendocrine activation in response to stress also varies as a function of age.…”
Section: Introductionmentioning
confidence: 99%